Characteristics of Atmosphere-rice Paddy Exchange of Gaseous and Particulate Reactive Nitrogen in Terms of Nitrogen Input to a Single-cropping Rice Paddy Area in Central Japan - Kentaro Hayashi; Keisuke Ono; Kazuhide Matsuda; Takeshi Tokida; Toshihiro Hasegawa (Asian Journal of Atmospheric Environment, 2017)
Nitrogen (N) is an essential macronutrient. Thus, evaluating its flows and stocks in rice paddy ecosystems provides important insights into the sustainability and environmental loads of rice production. Among the N sources of paddy fields, atmospheric deposition and irrigation inputs remain poorly understood. In particular, insufficient information is available for atmosphere-rice paddy exchange of gaseous and particulate reactive N (Nr, all N species other than molecular N) which represents the net input or output through dry deposition and emission. In this study, we assessed the N inputs via atmospheric deposition and irrigation to a Japanese rice paddy area by weekly monitoring for 2 years with special emphasis on gas and particle exchange. The rice paddy during the cropping season acted as a net emitter of ammonia (NH3) to the atmosphere regardless of the N fertilizer applications, which reduced the effects of dry deposition to the N input. Dry N deposition was quantitatively similar to wet N deposition, when subtracting the rice paddy NH3 emissions from N exchange. The annual N inputs to the rice paddy were 3.2 to 3.6 kg N ha-1 yr-1 for exchange, 8.1 to 9.8 kg N ha-1 yr-1 for wet deposition, and 11.1 to 14.5 kg N ha-1 yr-1 for irrigation. The total N input, 22.8 to 27.5 kg N ha-1 yr-1, corresponded to 38% to 55% of the N fertilizer application rate and 53% to 67% of the brown rice N uptake. Monitoring of atmospheric deposition and irrigation as N sources for rice paddies will therefore be necessary for adequate N management.